MENGAPA TENAGA PENGAJAR PRODI KEPERAWATAN DI YOGYAKARTA TIDAK MEMENUHI STANDAR AKREDITASI BAN PERGURUAN TINGGI? - Nurul Isnaini F.; Hari Kusnanto; Mubasysyir Hasanbasri (Journal of Health Service Management, 2016)
Background: The main factor that determines the quality ofeducation in higher education is the quality of the lecturers in it.Quality nursing services need to be supported by nursingresources that are produced from quality educationalinstitutions according to established standards. In fact, thecurrent nursing education does not have a national standard sothat the quality of its graduates varies.Objective: This study aimed to describe and determine thecharacteristics of the lecturers that include educationalqualifications, functional, certification, and the ratio of faculty innursing studies program and see the extent to which facultycontribute to meet the accreditation status of private nursingstudies program in Yogyakarta.Methods: Analysis of a cross sectional quantitative data byunivariate analysis.Result: The status of accreditation in private nursing courses inYogyakarta (40%) accreditation of B and (60%) accreditedprograms C. length stand of Nursing program did'nt showevidence of accreditation better. Based on the educationalqualifications of teachers who are eligible according to thestandard Accreditation B (35%), which does not meet thestandards yet accredited B (5%), the variable functional and nolecturer certification courses that meet the standards of BAN PT.The ratio of lecturers in private nursing studies program is stillnot ideal proved to be only 10% of nursing study program thathas a good ratio. From observations and interviews obtainedevidence several nursing program still face many obstacles inimproving the quality of human resources and implementationof accreditation.Conclusion: The status of accreditation of private nursing inYogyakarta is still low, faculty of Nursing Prodi also still don'tmeet the qualifications in accordance with Law 14 of 2005. Ittakes a strong commitment from study program organizers andthe government to foster private nursing colleges in Yogyakarta.